THE SCRAPBOOK FOR THE STUDENTS' WRITING ABILITY AT JUNIOR HIGH SCHOOL (A CASE STUDY AT JUNIOR HIGH SCHOOL) - Mariyatul Kiptiyah; Untung Untung (Universitas Madura, 2023)
Writing involves textual tasks like formulating and structuring ideas into sentences, encompassing idea creation, organization, drafting, and revision. In this context, the utilization of scrapbooks as a teaching aid for writing has yielded positive results, introducing a novel method for writing instruction. This practice not only improves students' recount text abilities but also highlights the versatility of scrapbooks in catering to multiple skills, as revealed by the interview results—spanning both writing and speaking instruction. Embracing scrapbooks in education holds the potential to foster holistic language development and effective communication skills, thereby enriching the learning experience across various linguistic domains. In this research, the researcher used qualitative with case studied approach.